Finance and economy for society : integrating sustainability - Alijani, Sharam; Karyotis, Catherine (Critical studies on corporate responsibility, governance and sustainability ;, 2017)
The latest volume of Critical Studies on Corporate Responsibility, Governance and Sustainability examines the social, economic and environmental impacts of corporations, and the real effects of corporate governance, CSR and business sustainability on societies in different regions.--